Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized for You

we will pick new questions that match your level based on your Timer History

Track Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

It appears that you are browsing the GMAT Club forum unregistered!

Signing up is free, quick, and confidential.
Join other 500,000 members and get the full benefits of GMAT Club

Registration gives you:

Tests

Take 11 tests and quizzes from GMAT Club and leading GMAT prep companies such as Manhattan GMAT,
Knewton, and others. All are free for GMAT Club members.

Applicant Stats

View detailed applicant stats such as GPA, GMAT score, work experience, location, application
status, and more

Books/Downloads

Download thousands of study notes,
question collections, GMAT Club’s
Grammar and Math books.
All are free!

Thank you for using the timer!
We noticed you are actually not timing your practice. Click the START button first next time you use the timer.
There are many benefits to timing your practice, including:

What we know:
h = hyp
b = base
p = perpendicular
p┬▓ + b┬▓ = h┬▓

(1) So we know that p = h - 6, using this information we get:
(h - 6)┬▓ + b┬▓ = h┬▓
h┬▓ - 12h + 36 + b┬▓ = h┬▓
b┬▓ = 12h - 36
b = 12, b = (h - 3) .... b = (h - 3) is what's given in statement 2, we can use this information to figure out h = 15 and so p = 9

(2) We know b = h - 3, using this information we can use the substitution like the one in Statement 1 to figure out h = 15 and b = 12

So the triangle ends up being (9, 12, 15). For sanity check if you use both statements you'll see that h = 15 and h = 3. But we can't use h = 3 because that doesn't satisfy out conditions given in the DS statements.

But if you use b = h-3 in step (1), arent you using information from (2) in the question, making your answer C instead of D?

Not exactly, because you got this information on your own by using information provided only in current statement. The other thing is, in GMAT end information has to be agreed on by both statements so by that virtue you can still get away with having the same information that would be provided in the other statement.

b = 12, b = (h - 3) .... b = (h - 3) is what's given in statement 2, we can use this information to figure out h = 15 and so p = 9 above you say that you are using the info from statement 2 and then you say .... "Not exactly, because you got this information on your own by using information provided only in current statement."

in GMAT end information has to be agreed on by both statements what does it mean. Please give an example.

Also us say
What we know: h = hyp b = base p = perpendicular p┬▓ + b┬▓ = h┬▓ but then while solving you interchange b and h; eg. statement 1 says "Difference of hypotenuse and base is 6 inches. " but in your solution you have "(1) So we know that p = h - 6, using this information we get: "

I have just come back from office after a long day ... so ....am I going crazy or just missing the point here?

What we know: h = hyp b = base p = perpendicular p┬▓ + b┬▓ = h┬▓

(1) So we know that p = h - 6, using this information we get: (h - 6)┬▓ + b┬▓ = h┬▓ h┬▓ - 12h + 36 + b┬▓ = h┬▓ b┬▓ = 12h - 36 b = 12, b = (h - 3) .... b = (h - 3) is what's given in statement 2, we can use this information to figure out h = 15 and so p = 9

wonder , p = h -6 is wrong ... in 1. b= h -6 is the correct relationship.

Also, you need to check how you get b = 12 , b = h-3?

Quote:

(2) We know b = h - 3, using this information we can use the substitution like the one in Statement 1 to figure out h = 15 and b = 12

So the triangle ends up being (9, 12, 15). For sanity check if you use both statements you'll see that h = 15 and h = 3. But we can't use h = 3 because that doesn't satisfy out conditions given in the DS statements.

here again..you switch it... we need p =h-3.

Wonder, you want to take a look now... if you get a different answer?

Thanks
Praetorian

Last edited by Praetorian on 12 Dec 2003, 23:46, edited 2 times in total.

a simplification gives....9 + 2 hp = p ^2 ...............(b)

Again, clearly insufficient

Combine..from (a) and (b).... 36 + 2 hb = 9 + 2hp
27 = 2h (p - b)
b = h - 6 , p = h- 3
p - b = 3
27 = 6h get h = 27 .. the rest can be calculated one hyp is known

Answer C

addendum : i think this problem can be solved easily if we see that we have three unknowns and each of the choices only gives us information about two. so we might want to skip directly to the "combine" step.

What we know: h = hyp b = base p = perpendicular p┬▓ + b┬▓ = h┬▓

(1) So we know that p = h - 6, using this information we get: (h - 6)┬▓ + b┬▓ = h┬▓ h┬▓ - 12h + 36 + b┬▓ = h┬▓ b┬▓ = 12h - 36 b = 12, b = (h - 3) .... b = (h - 3) is what's given in statement 2, we can use this information to figure out h = 15 and so p = 9

wonder , p = h -6 is wrong ... in 1. b= h -6 is the correct relationship.

Also, you need to check how you get b = 12 , b = h-3?

Quote:

(2) We know b = h - 3, using this information we can use the substitution like the one in Statement 1 to figure out h = 15 and b = 12

So the triangle ends up being (9, 12, 15). For sanity check if you use both statements you'll see that h = 15 and h = 3. But we can't use h = 3 because that doesn't satisfy out conditions given in the DS statements.

here again..you switch it... we need p =h-3.

Wonder, you want to take a look now... if you get a different answer?

Thanks Praetorian

Yes, I switched the variables by mistake. Sorry about that. But that shouldn't matter, the answer is still the same.

What we know: h = hyp b = base p = perpendicular p┬▓ + b┬▓ = h┬▓

(1) So we know that p = h - 6, using this information we get: (h - 6)┬▓ + b┬▓ = h┬▓ h┬▓ - 12h + 36 + b┬▓ = h┬▓ b┬▓ = 12h - 36 b = 12, b = (h - 3) .... b = (h - 3) is what's given in statement 2, we can use this information to figure out h = 15 and so p = 9

wonder , p = h -6 is wrong ... in 1. b= h -6 is the correct relationship.

Also, you need to check how you get b = 12 , b = h-3?

Quote:

(2) We know b = h - 3, using this information we can use the substitution like the one in Statement 1 to figure out h = 15 and b = 12

So the triangle ends up being (9, 12, 15). For sanity check if you use both statements you'll see that h = 15 and h = 3. But we can't use h = 3 because that doesn't satisfy out conditions given in the DS statements.

here again..you switch it... we need p =h-3.

Wonder, you want to take a look now... if you get a different answer?

Thanks Praetorian

Yes, I switched the variables by mistake. Sorry about that. But that shouldn't matter, the answer is still the same.

how is the answer same?

it should be C , not D

what did i do wrong ..could you check my post in this thread.